Prática de análise linguística (crítica) no contexto de formação inicial de professores de Língua Portuguesa: uma abordagem em construção - Barreto, Taís Vasques (2022)
This research derives from the author's personal and academic concerns regarding the comprehension and the borrowing of Practice of Linguistic Analysis (PAL, for the acronym in Portuguese) by elementary and high school teachers in formation. One analyzed how teachers in formation understand PAL and recontextualize it in didactic activities. In order to do so, one established as the aim of the research to analyse to what extent Portuguese teachers in initial formation enrolled in the academic subject entitled “Reading and Text Production – Practice of Linguistic Analysis in School Context” comprehend and borrow PAL. One established as specific objectives: i) to identify, in the light of the Systemic-Functional Grammar, the discursive representations of teachers in initial formation about PAL; ii) to verify to what extent teachers in initial formation borrow PAL in the execution of didactic activities in the context of the subjects taught; iii) to verify to what extent PAL proposed by the undergraduates is close to a critical approach. The study is based on theoretical-methodological assumptions of PAL for didactic purposes (GERALDI, 1984; 1991; 1999; 2015; FRANCHI, 1991; MENDONÇA, 2006) and on Critical Analysis of Gender (AGC, for the acronym in Portuguese), which considers the uses of language as situated practices (MOTTA-ROTH, 2008; BAZERMAN, 2006; 2009; FAIRCLOUGH, 2016; HALLIDAY and MATHIESSEN, 2014). Of a qualitative nature, the methodological course undertaken presents as research procedure a case study and makes its object of analysys the aforementioned subject. The undertaking of didactic activities by five teachers in initial formation, who took part of the research as volunteers, constituted the object of the case study. The corpora of this dissertation consisted of responses to a diagnostic instrument and of the production of didactic activities in the course of the aforementioned academic subject. The analysis of the collected data revealed three discursive representations of PAL as understood and borrowed by the participants: i) as a mean of opposition to the teaching of traditional grammar (they are different practices); ii) as a mean of practicing epilanguage (it promotes a reflection on the language); and iii) as critical thinking (it develops, to some extent, the student's critical sense). The analysis of the didactic activities revealed the use by the teachers of the practice of reading as the main tool to develop the student's critical sense for the use of languague, but not necessarily an articulation of it with PAL. In this way, PAL prioritizes the description and identification of expressive resources based on metalanguage and, therefore, does not promote a reflection that enables the inductive construction of linguistic knowledge. In addition, it was found that there is a certain fragility in relation to the approach of gender as a teaching unit and that the participants seem not to be able to articulate the strata of language in a clear and coherent way. Based on that, in this dissertation, in order to promote advances for the formation of teachers, one proposes an essay on PAL in a critical approach, which finds its theoretical-methodological support in ACG to suggest a possible practice of teaching that aims to analyze the language in use in a critical and reflexive way .